EFFECT OF ”KOMBA-KOMBA” PRUNING COMPOST AND PLANTING TIME OF MUNGBEAN IN INTERCROPPING WITH MAIZE ON YIELD AND SOIL FAUNA - Laode Sabaruddin; Laode Muhammad Harjoni Kilowasid; Hasbullah Syaf (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2013)
Soil fauna plays an important role in decomposition and nutrient mineralization. The objective of this research was to study the effect of